Broadening the Dental Hygiene Students' Perspectives on the Oral Health Professionals: A Text Mining Analysis - Yukiko Nagatani; Rintaro Imafuku; Yukie Nakai (MDPI AG, 2022)
Professional identity formation, an important component of education, is influenced by participation, social relationships, and culture in communities of practice. As a preliminary investigation of dental hygienists' professional identity formation, this study examined changes in the dental hygiene students' perceptions of oral health professionals over the three years of their undergraduate program. At a Japanese dental hygiene school, 40 students participated in surveys with open-ended questions about professional groups several times during their studies. The text data were analyzed through content analysis with text mining software. The themes that characterized their dental hygienist profession perceptions in their programs each year were identified as: "Supporters at the dental clinic"; "Engagement with interprofessional care" and "Improved problem-solving skills for clinical issues regarding the oral region"; and "Active contribution to general health" and "Recognition of the roles considering relationships" (in the first, second, and third years, respectively). The students acquired professional knowledge and recognized the significance and roles of oral health professionals in practice. They gained more learning experiences in their education, including clinical placements and interprofessional education. This study provides insight into curriculum development for professional identity formation in dental hygiene students.